2019
DOI: 10.21608/asejaiqjsae.2019.69475
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Phytochemical Studies on Brown Algae Sargassum muticum from Marsa Alam at Red Sea Coast, Egypt

Abstract: The present investigation revealed that Red sea stretches along Marsa Alam of Egypt is a habitation of diverse groups of marine macro-algal species recorded along Marsa Hemera shore. Ecological studies (meteorological data, water, soil, aqueous extract analysis of Sargassum muticum (Yendo) Fensholt and associated species) reported that, slightly alkaline; low turbidity, moderate temperature and available nutrient content of saline water produced massive growth of S. muticum during September (2018). Ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…The levels of both phosphorus and potassium in the 'Mixed Sargassum' were above the maximum levels found by Rodríguez-Martínez et al [43]. The levels of cadmium, chromium, copper, lead and manganese in the current study were similar to those found in S. muticum [86]. Chen et al [84] in a study of 295 brown and red seaweed samples found that elements in seaweeds can be listed in descending order of mean concentration: Al > Mn > As > Cu > Cr > Cd > Pb > Hg, but this study found a slightly different order of As > Al > Mn > Cu > Pb > Cr > Cd > Hg with both arsenic and lead being higher in the relative order.…”
Section: Minerals and Metalssupporting
confidence: 75%
“…The levels of both phosphorus and potassium in the 'Mixed Sargassum' were above the maximum levels found by Rodríguez-Martínez et al [43]. The levels of cadmium, chromium, copper, lead and manganese in the current study were similar to those found in S. muticum [86]. Chen et al [84] in a study of 295 brown and red seaweed samples found that elements in seaweeds can be listed in descending order of mean concentration: Al > Mn > As > Cu > Cr > Cd > Pb > Hg, but this study found a slightly different order of As > Al > Mn > Cu > Pb > Cr > Cd > Hg with both arsenic and lead being higher in the relative order.…”
Section: Minerals and Metalssupporting
confidence: 75%
“…Sargassum muticum was collected from Marsa Alam, Red Sea, Egypt, and immediately transported in plastic bags containing seawater to the laboratory to stop the degradation of the alga. The identified alga by Jha et al (2009) and Azzazy et al (2019) (Figure 1), were extensively washed with sterilized seawater to remove foreign materials. The specimen was dried in the shade until constant weight and was blended into a powder.…”
Section: Collection Of Sargassum Muticummentioning
confidence: 99%
“…Macroalgae are known to be a wealthy source of dietary fiber, essential amino acids, nutrients, vitamins, antioxidants and lipids [ 3 , 17 ]. Thus, they are valuable natural sources for fertilizers and plant growth regulators, food commodities, animal feeds and perform a crucial role in agriculture and horticulture [ 18 , 19 ]. Recently, seaweeds have also been used for a variety of purposes, including health benefits, biofuel production, cosmetics, pharmaceuticals, textiles and bioplastic packaging [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%